THE EFFECTS OF TEAM GAMES TOURNAMENT ON THE TEACHING OF VOCABULARY FOR THE FOURTH GRADERS OF SDN 1 MENGANTI (RETAIN, 2013)
Vocabulary is important to be considered because it is the main component to develop a language. It also has an important role for the four language skills. As we know, English vocabulary has different sound in their pronunciation and spelling that it is different from Bahasa Indonesia as our first language. That makes the students of elementary schools as young learners still lack of vocabulary. It means that they need vocabulary development. Then, it will be easier for them to learn the four English basic skills, which are listening, speaking, reading, and writing. To help the students learning vocabulary easily, the teacher can choose their technique and media which is appropriate and can interest the students. One of the methods that can be used to achieve their goal of study is Team Games Tournament. Team Games Tournament makes the students work in their groups and have a competition in the tournament. In each team, there are students who have different ability in learning English. So the students who have the higher ability can motivate their other friends and share their knowledge so that each member of the group can understand the material. There are also dimensions of excitement contributed by the use of games on the tournament. The teammates help each other to prepare the games by studying the worksheet and explain the problem and the material to each member of them. However, if they are in the tournament, they may not help each other to train their individual responsibility. Through this study, the researcher tried to explore the effectiveness of Team Games Tournament to teach vocabulary for the fourth graders. The subjects of this study were fourth graders of SDN 1 Menganti. The subjects were divided into two groups, experimental group and control group. These two groups were given a pretest in order to know their ability. After treatment was given to the experimental group, they were given posttest. Based on the data from the pretest of both groups, it was found that the experimental and control groups have the same ability. On the other hand, the score of experimental group were higher than control group on posttest. From the calculation of t-test, it was found that there was significant difference between experimental and control groups. The result also answered the research question of this study. Key words: Vocabulary, Fourth Graders, Team Games Tournament